Disaster medicine: учебник для использования в образовательных учреждениях, реализующих основные профессиональные образовательные программы высшего образования по направлениям подготовки специалитета 31.05.01 "Лечебное дело" - Гаркави, А. В. Андрей Владимирович (Sechenov university, 2019)
This textbook addresses the issues of treatment of victims with mechanical and thermal lesions in different emergency situations. Life threatening conditions are analyzed in detail - their pathogenesis, prevention and emergency care. Particular attention is paid to the algorithms of diagnostic triage, prehospital medical care and first aid. The outlined material is provided with explanatory diagrams and illustrations. Each section of the book ends with various self-control assignments as well as situational tasks. The textbook is intended for medical students and matches the interest of a wide range of medical practitioners.